Observations from the post-COVID-19 cardiovascular examination record - Ruiz, Aurora (2023)
Objective: To evaluate the prevalence and characteristics of “de novo” cardiovascular findings (DNCFs) among post-COVID patients based on a basic cardiovascular diagnostic procedure. Moreover, to describe the patients’ results obtained by means of different diagnostic methods, to determine the clinical variables associated with DNCFs during the examination and, finally, to find out the diagnostic value of different data from the medical records (MRs). Materials and methods: Patients aged > 18 years who had COVID-19 either at the hospital or at home were evaluated by clinical interviews, physical examination, electrocardiogram (EKG), echocardiogram, routine lab tests and cardiac biomarkers between 30 and 120 days after discharge. A total of 246 patients (age: 52 ± 13 years; women: 48 %; mild, moderate and severe COVID-19: 37 %, 39 % and 24 %, respectively) were included in the study. Twenty-four percent of the population were asymptomatic at the time of the evaluation. In those patients who developed symptoms, dyspnea was the most frequent one (28 %). Interviews were the method with the highest index of suspicion (45 %). Physical examination, EKG, echocardiogram and biomarkers showed normal values among 61 %, 60 %, 75 % and 96 % of the patients, respectively. Results: DNCFs were found in 62 patients (25.2 %): heart rhythm disorders in 42 (17 %) and ventricular dysfunction in 20 (8 %). Five patients had coronary artery disease, six had myocarditis and two had valvular heart disease. In addition, post-COVID pulmonary embolism (PE) was detected in 10 patients, six of whom (2.4 %) had to be rehospitalized. Furthermore, in a multivariate analysis, the independent predictive variables of DNCFs were prior history of chronic obstructive pulmonary disease (COPD), QTc > 440 msec, leukocytosis and intra-COVID cardiovascular complication. MRs showed both low sensitivity and positive predictive value for DNCFs. Conclusions: Although DNCFs were observed in 25 % of the population, only 2 % were significant. According to the data collected from this diagnostic procedure and in this time frame, special attention should be paid to patients with prior history of COPD and/or cardiovascular complications during the acute stage and/or prolonged QTc interval. Post-COVID symptoms were of limited value for the diagnosis of arrhythmias or ventricular dysfunction.